Health : the basics - Donatelle, Rebecca J. (San Francisco : Benjamin Cummings, 2003)
This book emphasizes the essential health information necessary to develop a comprehensive understanding of health promotion and disease prevention from a behavioral management perspective.
Includes references and index.
Keywords: Health; Public Health